Unconventional Fiscal Policy, Inflation Expectations, and Consumption Expenditure - Francesco D'Acunto; Daniel Hoang; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2016)
Unconventional fiscal policies incentivize households to accelerate consumption by generating future consumer price ination, and offer an alternative to unconventional monetary policy (Correia et al. (2013)). We use a natural experiment to study the causal effect of unconventional fiscal policies on consumption expenditure via the inflation-expectations channel. The German administration unexpectedly announced in November 2005 a three-percentage-point increase in value-added tax (VAT) effective in 2007. This shock increased German households' inflation expectations during 2006, as well as actual inflation in 2007. Matched households in other European countries serve as counterfactuals in a difference-in-differences identification design. German households' willingness to purchase durable goods increased by 34% after the shock, compared to matched foreign households. Income or wealth effects do not appear to drive these results, and we do not find evidence of intratemporal substitution from non-durable to durable consumption.
Keywords: D12; D84; D91; E21; E31; E32; E52; E65; 330; durable consumption; zero lower bound; fiscal and monetary policy; survey data